2007
DOI: 10.1021/ma062727z
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystals of the Poly(l-lactide) Block and the Poly(ethylene glycol) Block in Poly(l-lactide)−poly(ethylene glycol) Diblock Copolymer

Abstract: Single crystals of the poly(l-lactide) (PLLA) block and the poly(ethylene glycol) (PEG) block in poly(l-lactide)−poly(ethylene glycol) diblock copolymer were obtained by melt crystallization. The morphology, structure, and evolution process of the single crystals were investigated using transmission electron microscopy (TEM), selected-area electron diffraction (SAED), and real-time atomic force microscopy (AFM). Two types of crystal morphology were obtained. One was the regular morphology of a single crystal: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 38 publications
2
64
1
Order By: Relevance
“…This makes the crystallizable block copolymers representative systems having confined crystallization behavior, especially in the strong segregation regime [52]. Confined crystallization has been widely observed in the diblock copolymers having double crystalline blocks, such as PEO-b-PCL [112][113][114][115][116], PLLA-b-PEO [117][118][119][120][121][122], PLLA-b-PCL [123][124][125], poly(p-dioxanone) (PPDX)-b-PCL [126][127][128], polyolefin-based block copolymers [129][130][131][132][133][134][135], and so on. The confined crystallization kinetics and crystalline morphology of such block copolymers have been extensively studied.…”
Section: Crystalline Morphology Of Polymer Segments Confined In Blockmentioning
confidence: 99%
“…This makes the crystallizable block copolymers representative systems having confined crystallization behavior, especially in the strong segregation regime [52]. Confined crystallization has been widely observed in the diblock copolymers having double crystalline blocks, such as PEO-b-PCL [112][113][114][115][116], PLLA-b-PEO [117][118][119][120][121][122], PLLA-b-PCL [123][124][125], poly(p-dioxanone) (PPDX)-b-PCL [126][127][128], polyolefin-based block copolymers [129][130][131][132][133][134][135], and so on. The confined crystallization kinetics and crystalline morphology of such block copolymers have been extensively studied.…”
Section: Crystalline Morphology Of Polymer Segments Confined In Blockmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] One prominent system is a diblock copolymer composed of poly(ethylene oxide) (PEO) and poly(ε-caprolactone) (PCL) because of their biocompatibility, biodegradability, and reasonable strength. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] These properties are derived from both their chemical structure as well as their physical structures. Because both PEO and PCL are semicrystalline polymers, their crystallinity greatly affects their mechanical and biorelated properties; therefore, it is important to understand how their crystals grow in this unique architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have also been shown for thin film growth of PEO-b-poly(L-lactide) (PLLA) copolymers with identical molecular weights between the two blocks. [18][19][20][21] Here, the PLLA crystallizes first due to a higher crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the T c -dependent morphological behavior of the asymmetric copolymers is the result of soft confinement crystallization. It has been confirmed that the PEO-b-PLA copolymers are disordered in the melt [6,10,55]; the two components, PLA and PEO blocks, are weakly segregated. Microphase separation of the copolymers is driven by the crystallization of PLA block, which will influence the diffusion PLA component, growth and orientation of PLA lamellae.…”
Section: Soft Confined Crystallization and Microphase Separation-detementioning
confidence: 91%
“…The crystalline morphology is formed by stacking flat-on growing lamellae in the thin film. Lozenge-shaped single crystal with screw dislocation of PLA has been reported in thin film of PLA or its copolymers that the thickness is less than 100 nm [6,7,12,[55][56][57]. However, the special crystalline morphology of hexagonal dendrite stacked with PLA single crystals has never been reported.…”
Section: Dendritic Superstructures and Structure Transitions In Peo-bmentioning
confidence: 99%